Aerobic versus isometric handgrip exercise in hypertension: a randomized controlled trial. Issue 11 (November 2017) - Pagonas, Nikolaos; Vlatsas, Stergios; Bauer, Frederic; Seibert, Felix S.; Zidek, Walter; Babel, Nina; Schlattmann, Peter; Westhoff, Timm H.
Abstract : Objectives: Aerobic dynamic exercise reduces blood pressure (BP) and is broadly recommended by current American and European hypertension guidelines. Isometric exercise is currently not recommended, since data from only a few studies are available. We compare for the first time the effects of isometric handgrip training and aerobic exercise in a randomized controlled trial. Methods: A total of 75 hypertensive patients were randomized to one of the following 12-week programmes: Isometric handgrip training five times weekly (two contractions of 2 min at 30% of maximal power with each arm); 'Sham-handgrip training' five times weekly (two contractions of 2 min at 5% of maximal power with each arm); Aerobic exercise training of 30 min three to five times per week. All patients underwent office BP measurement, 24-h ambulatory BP measurement and noninvasive assessment of arterial compliance and systemic vascular resistance at baseline and after 12 weeks. Results: Baseline epidemiological and hemodynamic characteristics did not differ between groups. Aerobic exercise led to a significant reduction of systolic 24-h BP ( P = 0.025), office SBP ( P = 0.03), systemic vascular resistance ( P = 0.001) and small artery elasticity index ( P = 0.005). There were no statistical significant changes of these parameters in the isometric exercise and the 'sham exercise' groups ( P > 0.05 each). Conclusion: Isometric handgrip training, performed according to a typical protocol, did not reduce BP in hypertensive patients. Aerobic exercise, even as an uncontrolled and unsupervised exercise regimen, led to a significant reduction of ambulatory and office BP. Abstract : Supplemental Digital Content is available in the text